Analysis of voltage-lift-type boost converters - Zhu, Miao (2013)
This paper introduces a set of positive output boost dc-dc converters applying the series voltage-lift technique. Compared with the traditional boost converter, the proposed circuits can perform positive-to-positive dc-dc voltage increasing conversion with higher voltage conversion ratios. They are different from other existing dc-dc step-up converters and are featured with the single-switch operation in simple structures. Since the proposed converters avoid using transformers and cascade connection, their relative simple structures are beneficial to potential industrial applications in future. A detailed theoretical analysis for both continuous and discontinuous conduction modes is given, which is verified by the simulation results.